The Haunted World of El Superbeasto (Rob Zombie, 2009): An Animated Exploitation of Exploitation Cinema - Pierre Floquet (Transatlantica)
It could be argued that, like any exploitation movie, Rob Zombie’s 2009 animation film, while dealing with transgressive issues, relies on scandalous material in order to “exploit” specific niche audiences. Yet the question remains as to whether the movie also means to play a controversial political role in showing what Hollywood films (both direct and animated) have repressed—the unseen of culture—or whether it is merely a distanced animated one-off in the directing career of a multi-skilled artist. This animation film is not just an adaptation of the eponymous graphic novel, but, rather, an exploitation of the tricks and clichés of exploitation cinema in the form of animated cinema. Beyond wrestling, it slashes through several sub-genres, including Nazisploitation, bikerfilms, sexploitation and more, making it a carnivalesque ride. Because the medium of animation highlights and intensifies any original code of representation, the film ultimately questions the mise en abyme of cinema within exploitation films, as much as films within animation films. By crossing and blurring the boundaries between these various cinematic forms, Rob Zombie incidentally raises the issue of defining animation within cinema at large, all the while promoting a somewhat ambiguous, reactionary discourse in spite of his own politics.